Second generation bioethanol potential from selected Malaysia's biodiversity biomasses: A review - Aditiya H.B.; Chong W.T.; Mahlia T.M.I.; Sebayang A.H.; Berawi M.A.; Nur H. (Elsevier Ltd, 2023)
Agricultural wastes; Agriculture; Air quality; Biodiversity; Bioethanol; Cellulose; Ethanol; Feedstocks; Fruits; Palm oil; Proven reserves; Starch; Ethanol yield; Forestry biomass; Global temperatures; Oil palm; Oil palm biomass; Organic sources; Second generation bioethanol; Starch compounds; Biomass; bioethanol; biomaterial; feedstock; lignocellulose; starch; unclassified drug; alcohol; biofuel; cellulose; hemicellulose; polysaccharide; biofuel; biomass; fossil fuel; fruit; literature review; paddy field; agricultural waste; banana; biomass production; chemical composition; Elaeis; energy consumption; forestry; Malaysia; pineapple; priority journal; renewable energy; Review; rice; angiosperm; biomass; metabolism; Malaysia; Ananas comosus; Durio zibethinus; Elaeis; Angiosperms; Biofuels; Biomass; Cellulose; Ethanol; Malaysia; Polysaccharides; Starch